Impact of biogenic very short-lived bromine on the Antarctic ozone hole during the 21st century ... : تأثير البروم الحيوي قصير العمر للغاية على ثقب الأوزون في أنتاركتيكا خلال القرن <></ sup> الحادي والعشرين ... - Rafael P. Fernández; Douglas E. Kinnison; Jean‐François Lamarque; Simone Tilmes; Alfonso Saiz‐Lopez (OpenAlex, 2016)
Abstract. Active bromine released from the photochemical decomposition of biogenic very short-lived bromocarbons (VSLBr) enhances stratospheric ozone depletion. Based on a dual set of 1960–2100 coupled chemistry-climate simulations (i.e. with and without VSLBr), we show that the maximum Antarctic ozone hole depletion increases by up to 14 % when natural VSLBr are considered, in better agreement with ozone observations. The impact of the additional 5 pptv VSLBr on Antarctic ozone is most evident in the periphery of the ozone hole, producing an expansion of the ozone hole area of ~5 million km2, which is equivalent in magnitude to the recently estimated Antarctic ozone healing due to the implementation of the Montreal Protocol. We find that the inclusion of VSLBr in CAM-Chem does not introduce a significant delay of the modelled ozone return date to 1980 October levels, but instead affect the depth and duration of the simulated ozone hole. Our analysis further shows that total bromine-catalysed ozone ... : الخلاصة: يعزز البروم النشط المنطلق من التحلل الكيميائي الضوئي لمركبات البروموكربون الحيوية قصيرة العمر (VSLBr) استنفاد الأوزون في الستراتوسفير. استنادًا إلى مجموعة مزدوجة من عمليات محاكاة الكيمياء والمناخ المقترنة بين 1960 و 2100 (أي مع وبدون VSLBr)، نظهر أن الحد الأقصى لاستنفاد ثقب الأوزون في أنتاركتيكا يزداد بنسبة تصل إلى 14 ٪ عند النظر في VSLBr الطبيعي، بما يتفق بشكل أفضل مع ملاحظات الأوزون. يتجلى تأثير 5 pptv VSLBr الإضافي على الأوزون في أنتاركتيكا بشكل أكثر وضوحًا في محيط ثقب الأوزون، مما ينتج عنه توسع في مساحة ثقب الأوزون تبلغ حوالي5 ملايين كيلومتر مربع، وهو ما يعادل حجم شفاء الأوزون في أنتاركتيكا الذي تم تقديره مؤخرًا بسبب تنفيذ بروتوكول مونتريال. نجد أن إدراج VSLBr في CAM - Chem لا يؤدي إلى تأخير كبير في تاريخ عودة الأوزون النموذجي إلى مستويات أكتوبر 1980، ولكنه يؤثر بدلاً من ذلك على عمق ومدة ثقب الأوزون المحاكى. يُظهر تحليلنا كذلك أن إجمالي تدمير الأوزون الناتج عن البروم في طبقة الستراتوسفير السفلى يتجاوز تدمير الكلور بحلول عام 2070، ويشير إلى أن كيمياء VSLBr الطبيعية ستهيمن على موسمية الأوزون في ...